Digital Transformation and Modernization with IBM API Connect - Kataoka, Bryon; Kataoka, Bryon; Brennan, James; Aggarwal, Ashish (Packt Publishing, 2022)
Successfully execute a strategic roadmap of digital transformation and modernize your enterprise with a proven API-led agile implementation approach by unlocking the full range of features in IBM API Connect Version 10Key FeaturesExplore techniques to design and deliver valuable customer-centric APIs using API ConnectManage your APIs with improved security and optimal performance across many channelsUncover hidden capabilities that help improve business agility and management within your API ecosystemBook DescriptionIBM API Connect enables organizations to drive digital innovation using its scalable and robust API management capabilities across multi-cloud and hybrid environments. With API Connect's security, flexibility, and high performance, you'll be able to meet the needs of your enterprise and clients by extending your API footprint. This book provides a complete roadmap to create, manage, govern, and publish your APIs. You'll start by learning about API Connect components, such as API managers, developer portals, gateways, and analytics subsystems, as well as the management capabilities provided by CLI commands. You'll then develop APIs using OpenAPI and discover how you can enhance them with logic policies. The book shows you how to modernize SOAP and FHIR REST services as secure APIs with authentication, OAuth2/OpenID, and JWT, and demonstrates how API Connect provides safeguards for GraphQL APIs as well as published APIs that are easy to discover and well documented. As you advance, the book guides you in generating unit tests that supplement DevOps pipelines using Git and Jenkins for improved agility, and concludes with best practices for implementing API governance and customizing API Connect components. By the end of this book, you'll have learned how to transform your business by speeding up the time-to-market of your products and increase the ROI for your enterprise.What you will learnUse API Connect to create, manage, and publish customer-centric, API-led solutionsRun CLI commands to manage API configuration and deploymentsCreate REST, SOAP, and GraphQL APIs securely using OpenAPISupport OAuth and JWT security methods using policiesCreate custom policies to supplement securityApply built-in policies to transform payloadsUse CLIs and unit testing hooks within DevOps pipelinesFind out how to customize Analytics dashboards and Portal User InterfaceWho this book is forThis book is for developers and architects who want to achieve digital transformation using IBM API Connect and successfully execute the strategic roadmap of enterprise modernization while effectively managing their API ecosystem. A solid understanding of what RESTful services and APIs can do and where to implement API security is necessary to get started. Experience in application development and basic knowledge of microservices, container orchestration, and cloud environments will help you to get the most out of this book.